Impact of Incentive Spirometry on Diaphragmatic Excursion in upper abdominal surgeries - Eman Yassin Salem, Ehab K Zayed1 , Magdy M Ahmed (International Journal of Scientific Research and Management (IJSRM), 2017)
Background and Aim of work: It is well known that upper abdominal surgeries resulted in restrictive pattern of breathing. The current study was conducted to investigate the effect of volume-oriented incentive spirometry on diaphragmatic excursion (D.E) during quite breathing (Q.B) and deep breathing (D.B) among patients undergoing elective upper abdominal surgery (UAS) Laparotomy cholecystectomy. Methods: Thirty male patients with ages ranged from 32 to 50 years with mean of 43.82 ± 5.51 who underwent UAS (Laparotomy cholecystectomies) participated in the study. Initially, all of them trained on deep breathing maneuver with incentive spirometry (IS) device, which provide a measurement of inspired volume. DE was measured during Q.B and D.B by Ultrasound (M mode) preoperatively and on the second postoperative day. Results: Postoperatively, D.E decreased significantly from 2.41 ± 0.6 mm. (preoperative.) to 1.5 ± 0.48 mm during Q.B, also it decreased from 6.38 ± 1.5 to 4.03 ± 1.4 during D.B. As well, the maximum inspired volume (MIV) reduced significantly postoperatively by 25.58%. D.E during D.B was correlated significantly with MIV (r = .561; R = 31) postoperatively, which does not correlate preoperatively. Conclusion: I.S maneuver resulted in significant increase in D.E during deep breathing after elective UAS.Also D.E contributed mainly to deep breathing maneuver through I.S post-operatively.